2008
DOI: 10.1007/s10593-009-0168-z
|View full text |Cite
|
Sign up to set email alerts
|

Cyclocondensation of N-aryl-3-oxobutanethioamides with 5-amino-3-R-4-R1-pyrazoles

Abstract: We have recently shown that N-aryl-3-oxobutanethioamides react with such 2-aminoazoles (azines) as 3-amino-5-R-1,2,4-triazoles [1], 2-amino-5-R-pyridines [2], 2-amino-4-R-5-R 1 -thiazoles [3], and 5-aminotetrazole [4] via a [3+3] cycloaddition scheme to form two groups of compounds (pyrimidine-4-thione and 4-(arylamino)pyrimidine derivatives) the ratio of which depends on the basicity of the heterocyclic 1,3-dinucleopile and the acidity of the solvent [1][2][3][4].The aim of this work is to continue our invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
9
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 5 publications
0
9
0
Order By: Relevance
“…Whilst the reactions of 3-oxopropanethioamides with 1,2-dinucleophiles and 1,2-and 1,3-dielectrophilic reagents were investigated earlier, recently it was shown that they can also react with nitrogen-containing 1,3-dinucleophiles of heterocyclic [71,[76][77][78][79] and acyclic [80] structures.…”
Section: [3+3] Cyclocondensation Of 3-oxopropanethioamides With 13-dmentioning
confidence: 99%
See 2 more Smart Citations
“…Whilst the reactions of 3-oxopropanethioamides with 1,2-dinucleophiles and 1,2-and 1,3-dielectrophilic reagents were investigated earlier, recently it was shown that they can also react with nitrogen-containing 1,3-dinucleophiles of heterocyclic [71,[76][77][78][79] and acyclic [80] structures.…”
Section: [3+3] Cyclocondensation Of 3-oxopropanethioamides With 13-dmentioning
confidence: 99%
“…It was established that N-aryl-3-oxobutanethioamides 144 undergo cyclization with 2-amino-5-R-pyridines [71], 3-amino-5-R-1,2,4-triazoles [76], 2-amino-4-R-5-R-thiazoles [77], 5-amino-3-R 1 -4-R 2 -pyrazoles [78], and 5-aminotetrazole [79] to form derivatives of 4-arylaminopyrimidine 145, 148, 150, and 151 and 4-pyrimidinethione 146, 147, 149, 152, and 153 [71,[76][77][78][79]. The reactions take place both in acetic acid [71,[76][77][78][79] and without a solvent [78][79][80].…”
Section: [3+3] Cyclocondensation Of 3-oxopropanethioamides With 13-dmentioning
confidence: 99%
See 1 more Smart Citation
“…[17] Later, Gewald developed the synthesis of 2-aminthiophenes, which became a characteristic pathway. [18][19][20] Three versions of the gewald reaction were reported (Scheme 1). The first version includes the aminecatalyzed condensation of an α-mercaptoaldehyde or ketone with acetonitrile bearing an electron-withdrawing group.…”
mentioning
confidence: 99%
“…[18,19,22,23] The third version was a two-step base-catalyzed synthesis that involves the formation of an α,β-unsaturated carbonitrile, which then reacts with sulfur for ring closure. [18,20] Other synthetic pathways for 2-aminothiophenes preparation have been reported in the literature. [20] Willgerodt-Kindler reaction is one of these pathways, which involves the preparation of 2-aminothiophenes from phenylbutanones in the presence of sulfur and amine solvent (Scheme 2).…”
mentioning
confidence: 99%